Analisis Beban Kerja pada Pegawai di Badan Kesatuan Bangsa dan Politik Kabupaten Karawang - Yobellika Br Depari; Budi Rismayadi; Wike Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the workload of employees at the Karawang Regency National and Political Unity Agency. The method used is qualitative with data collection techniques using interviews. The results showed significant variations in workload between employees, with some positions having high workloads. This shows the need to evaluate and adjust the balance of workload and loss of working time to increase employee efficiency and welfare. The implication is the need for additional human resources to ensure efficiency and effectiveness in carrying out work, as well as improvements in human resource management and increasing work efficiency at the Karawang Regency National and Political Unity Agency. The focus of this research also includes human resource management and workload to ensure suitability between workload and number of employees or positions.